2021
DOI: 10.2147/rmhp.s294786
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hospitalization Among Older Adults with COVID-19 in Saudi Arabia: A Cross-Sectional Study of a Nationally Representative Sample

Abstract: Background The aim of this study was to identify the predictors of hospitalization in older (≥60 years) patients with coronavirus disease-19 (COVID-19) in Saudi Arabia. Methods Patients were randomly selected from a COVID-19 database maintained by the Ministry of Health, Saudi Arabia. All patients were aged ≥60 years, had reverse transcriptase-polymerase chain reaction (RT-PCR)-confirmed COVID-19, and were registered in the database during March 2020 to July 2020. Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…While cardiovascular disease, a category inclusive of multiple individual conditions, has been identified as a risk factor for hospitalization and severe COVID-19 [ 2 , 10 , 15 ], it was not statistically significant in our multivariable analysis. Previous reports have found individual cardiac conditions (e.g., congestive heart failure, coronary artery disease, atrial fibrillation/arrythmia, and hypertension) to be associated with hospitalization [ 7 , 26 , 27 , 33 , 41 43 , 55 ]. Within this disease category, we found that history of hypertension or arrhythmia was associated with increased risk of hospitalization in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While cardiovascular disease, a category inclusive of multiple individual conditions, has been identified as a risk factor for hospitalization and severe COVID-19 [ 2 , 10 , 15 ], it was not statistically significant in our multivariable analysis. Previous reports have found individual cardiac conditions (e.g., congestive heart failure, coronary artery disease, atrial fibrillation/arrythmia, and hypertension) to be associated with hospitalization [ 7 , 26 , 27 , 33 , 41 43 , 55 ]. Within this disease category, we found that history of hypertension or arrhythmia was associated with increased risk of hospitalization in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We did not differentiate between type 1 and type 2 DM in our analysis, so we are unable to determine if the relationship between DM and COVID-19 hospitalization varies by type. Additionally, we had a lower number of patients with DM, which might have reduced our power to detect an association in multivariable analysis, as was reported in at least one other study [ 35 ] compared to studies where DM was reported to occur at a higher frequency and was found to be a risk factor for hospitalization [ 7 , 27 , 29 , 30 , 34 , 48 , 55 , 56 ]. Compared to other U.S. states, Colorado’s population is relatively healthy having the lowest proportion of adults with obesity and the fourth lowest percentage of residents with at least one of six underlying medical conditions found to be associated with an increased COVID-19 case fatality ratio in China [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the Ministry of Health (MOH) in Saudi Arabia confirmed that approximately 50 % of the COVID-related deaths among the critical cases present in an ICU were from among patients experiencing chronic diseases such as diabetes [ 40 ]. A recently published study stated that DM significantly more prevalent in hospitalized patients than in non-hospitalized patients, and patients with diabetes had a 52.1 % higher risk of hospitalization than patients without diabetes (OR = 1.52) [ 41 ].…”
Section: Why Diabetes Is Important?mentioning
confidence: 99%
“…The sample size was determined using G power software with an alpha of 0.05 (two-sided) and 90% power, the input parameter, and logistic regression. The sample size was calculated using different odds ratio values from a previous study 20 for different predictors (age, comorbidities, sex). The largest sample size was considered.…”
Section: Methodsmentioning
confidence: 99%